The Use of Kahoot! As an Arabic Teaching Media for Senior High School Students - Nur, Ifa Rodifah; Allafiony, Bachar; Rizqia, Ana Sabila (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
This study aims to determine the effectiveness of Kahoot teaching media in enhancing interest in learning the Arabic language among eleventh-grade students at Senior High School 1 Ngawi, East Java. The study utilized quantitative research methods with a quasi-experimental research design. The data for this research were collected from eleventh-grade students. The data collection involved interviews with teachers and respondents, as well as the distribution of questionnaires before and after using Kahoot for learning. Descriptive statistics and the Likert scale were employed for data analysis, along with hypothesis testing in the form of a t-test. The research results indicate that the use of Kahoot teaching media is effective in promoting interest in the Arabic language subject among eleventh-grade religious students at Senior High School 1 Ngawi. This is supported by the Independent Sample T-Test results, which show that the mean value of the experimental class (58.50) is greater than that of the control class (53.50), with a significance value (2-tailed) of 0.038, which is less than 0.05. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. تهدف هذه الدراسة إلى الكشف عن فعالية وسائل التعليم كاهوت في اهتمام التعلم اللغة العربية لدى طلاب الصف الحادي عشر المدرسة الثانوية 1 نجاوي جاوة الشرقية. استخدمت هذه الدراسة أساليب البحث الكمي مع تصميم البحث شبه التجريبي. مصدر البيانات في هذا البحث كان طلاب الصف الحادي عشر. تم جمع البيانات من خلال مقابلات مع المعلمين والمستجيبين وباستخدام استبيان تم توزيعه على المستجيبين قبل وبعد التعلم باستخدام الكاهوت. وتحليل البيانات المستخدمة هو الإحصاء الوصفي ومقياس ليكرت مع اختبار الفرضيات على شكل اختبار t. تدل نتائج البحث على أن استخدام وسائل التعليم كاهوت فعال لترقية اهتمام التعلم في مادة اللغة العربية للطلاب الفصل الحادي عشر الديني بالمدرسة العالية الإسلامية الحكومية الأولى نجاوي بدليل على أن نتائج الاختبار Independent Sampel T-Test على قيمة متوسطة للفصل التجريبي أكبر من الفصل الضابط بقيمة 58.50 > 53.50 بقيمة إشارة (2-ذيل) قدرها 0.038 < 0.05. فتم رفض فرضية Ho وتم قبول فرضية Ha.